2013
DOI: 10.1111/cdoe.12051
|View full text |Cite
|
Sign up to set email alerts
|

The role of potential mediators in racial inequalities in tooth loss: the Pró‐Saúde study

Abstract: There is an association between race and tooth loss that is mainly explained by current and early life socioeconomic variables, but not by behavioural factors and self-reported discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 38 publications
4
42
2
7
Order By: Relevance
“…33 The prevalence of self-reported discrimination was also higher than that found in studies that enrolled immigrants 9 and Latinos 34 in the United States; in both, the prevalence of discrimination was about 30.0%.…”
Section: Discussionmentioning
confidence: 66%
“…33 The prevalence of self-reported discrimination was also higher than that found in studies that enrolled immigrants 9 and Latinos 34 in the United States; in both, the prevalence of discrimination was about 30.0%.…”
Section: Discussionmentioning
confidence: 66%
“…The concept of estimating the effect of different factors and explaining tooth loss inequalities is not novel. In 2013, Celeste et al published a study with longitudinal data investigating ethnicity and tooth loss, and the mediating effect of behavioural factors. Their results showed that 1.4% of the ethnic inequality in tooth loss may be explained by the combination of dental visits, marital status, smoking and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a negative effect of alcohol consumption, whereas others found an inverse association between alcohol consumption and tooth loss . Previous studies included variables such as age, gender, smoking, alcohol consumption, dental plaque, and social determinants as confounding factors and applied change‐in‐estimate regression models to understand pathways in social inequality in tooth loss …”
Section: Introductionmentioning
confidence: 99%
“…The effect of ethnicity on health conditions is influenced by a set of factors. A study on tooth loss identified that the material conditions of life and educational levels were the most important factors [37]. Thus, it is necessary to investigate this difference between individuals with brown and black skin color in greater detail and evaluate whether Brazilian program of the quotas for blacks in universities (implanted in the last decade) may have also benefitted their health, as higher levels of schooling are commonly associated with a better health status [36,23,24,36].…”
Section: Discussionmentioning
confidence: 99%